THE EFFECT OF DIARY WRITING TECHNIQUE ON STUDENTS’ WRITING RECOUNT TEXT (A STUDY AT THE NINTH GRADE OF SMP KATOLIK FATIMA 2 SARUDIK 2020-2021 ACADEMIC YEAR) - Trylilis Libertine Baene (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract:The aim of this research are to know: 1) the application of diary writing technique on teaching writing recount text ability, 2) the students writing recount text ability before and after using diary writing technique, 3) Whether there is any significant effect of diary writing technique on teaching writing recount text ability at the ninth Grade Students of SMP Katolik Fatima 2 Sarudik. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the IX grade students’ of SMP Katolik Fatima 2 Sarudik which consist of 74 students. Sample were IX which consist of 32 students which taken by cluster sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The result of this research: 1) the application of diary writing technique was 3.5, it is categorized “Very Good”. 2) the mean score of the students’ writing recount text ability was 51,5 and it was categorized “bad”. Meanwhile, after using diary writing technique was 82,5, it is categorized “very good”. The result of data analysis shows that ttest was higher than ttable(ttest 18,59> ttable 2.03). So, the hypothesis was accepted. It means that, there is any significant effect of diary writing technique on students’ writing recount text ability at the IX grade students of SMP Katolik Fatima 2 Sarudik. Keywords: Diary Writing Tecnique, Writing Recount Text Ability